Interpreting thelanguage of histone and DNA modifications - Rothbart, Scott B. (2014)
A major mechanism regulating the accessibility and function of eukaryotic genomes are the covalent modifications to DNA and histone proteins that dependably package our genetic information inside the nucleus of every cell. Formally postulated over a decade ago, it is becoming increasingly clear that post-translational modifications (PTMs) on histones act singly and in combination to form a language or ‘code’ that is read by specialized proteins to facilitate downstream functions in chromatin. Underappreciated at the time was the level of complexity harbored both within histone PTMs and their combinations, as well as within the proteins that read and interpret the language. In addition to histone PTMs, newly-identified DNA modifications that can recruit specific effector proteins has raised further awareness that histone PTMs operate within a broader language of epigenetic modifications to orchestrate the dynamic functions associated with chromatin. Here, we highlight key recent advances in our understanding of the epigenetic language encompassing histone and DNA modifications and foreshadow challenges that lie ahead as we continue our quest to decipher the fundamental mechanisms of chromatin regulation.